1999
DOI: 10.1016/s0022-5223(99)70066-8
|View full text |Cite
|
Sign up to set email alerts
|

Pump-induced platelet aggregation in albumin-coated extracorporeal systems

Abstract: Pump perfusion of blood in coated systems elicits shear-induced platelet aggregation, which may be prevented by administration of substances that block the binding of von Willebrand factor to glycoprotein Ib receptors on the platelets. The effects of pumping on platelets are masked in uncoated circuits because of the dominant influence of blood-material contact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 26 publications
2
18
1
Order By: Relevance
“…Consistent with our findings, it was shown that incubation of blood with PVC slides results in rapid binding of leukocytes and platelets (27). Likewise, it is well known that in high-shear applications, in combination with blood activation, platelet deposition appears to be a major concern (24), as the in vitro flow of blood within uncoated tubes causes immediate platelet aggregation and loss (28).…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with our findings, it was shown that incubation of blood with PVC slides results in rapid binding of leukocytes and platelets (27). Likewise, it is well known that in high-shear applications, in combination with blood activation, platelet deposition appears to be a major concern (24), as the in vitro flow of blood within uncoated tubes causes immediate platelet aggregation and loss (28).…”
Section: Discussionsupporting
confidence: 89%
“…By monitoring platelet aggregation continuously, we were recently able to demonstrate that platelets in human and rat blood are activated by use of a roller pump. 16 Furthermore, when a simple coated tube was placed between the proximal part of a carotid artery and the distal part of a femoral artery in rats, pump-induced platelet aggregation was accompanied by systemic hypotension, and both could be prevented with aurintricarboxylic acid. This is a specific inhibitor of shearstress-induced platelet activation that blocks the binding of von Willebrand factor to platelet glycoprotein Ib.…”
mentioning
confidence: 99%
“…PF4 was found to be significantly higher for the test circuits with incubation chamber than for those without the chamber, and further increased when the blood was stressed by high occlusion of the roller pump. The increased activation with high occlusion can be attributed to shear-stressinduced platelet activation, 62 or as a secondary effect to ADP-induced platelet activation as a result of ADP release from lysed erythrocytes. The higher activation of platelets in the incubation setup with incubation chamber is apparently a consequence of the higher surface area in contact with blood and only secondly of the additional shear stress inside the streaming channel.…”
Section: Effect Of Pump Occlusion On Hemolysis and Plateletmentioning
confidence: 99%
“…The formation of PF4 in general was more pronounced in the perfusion chambers, as documented in Figure 14 in comparison to the screening chambers ( Figure 15). The stronger activation of thrombocytes during blood incubation in the perfusion chamber could be due to a shearstress-related thrombocyte activation 62 or related to the release of ADP of shear-stress-destroyed erythrocytes followed by an ADP-induced thrombocyte activation. Correspondingly, more adherent thrombocytes were observed on samples after incubation in the perfusion chambers.…”
Section: Comparison Of Screening and Perfusion Chambersmentioning
confidence: 99%